2022
DOI: 10.31083/j.jomh1810205
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Perceived Social Support and Sleep Quality among Older Men in Guangdong Province, China: The Mediating Role of Rumination and the Moderating Role of Physical Activity

Abstract: Background:The mental health status of older men is affected by several factors. Perceived social support, rumination, sleep quality, and physical activity are key factors that affect the mental health status of men over 60 years old. The mechanisms of their interactions have not been fully elucidated. The purpose of this research was to explore the relationship and interaction mechanisms among perceived social support, rumination, physical activity and sleep quality. The differences in physical activity level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
2
2
0
Order By: Relevance
“…Furthermore, The chances of poor sleep quality of the elderly without taking hypnotic drugs were 1.60 times more in persons with less social support than those with more social support (OR = 1.60, CI = 1.16–2.21). Consistent with the findings of the current research, Li et al (2022) found that older men receiving social support have decreased their worry levels and have promoted sleep quality [ 31 ]. Another study revealed that individuals who are receiving support from others; can reduce the effects of stress on sleep and improve sleep quality [ 32 ].…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, The chances of poor sleep quality of the elderly without taking hypnotic drugs were 1.60 times more in persons with less social support than those with more social support (OR = 1.60, CI = 1.16–2.21). Consistent with the findings of the current research, Li et al (2022) found that older men receiving social support have decreased their worry levels and have promoted sleep quality [ 31 ]. Another study revealed that individuals who are receiving support from others; can reduce the effects of stress on sleep and improve sleep quality [ 32 ].…”
Section: Discussionsupporting
confidence: 88%
“…Finally, the social isolation level of left-behind older adults can also affect IC through the chain mediating effect of perceived stress and health-promoting behavior. Our study results supported the findings of Li et al (17), i.e., perceived stress can affect healthy behavior. Stress levels are more closely related to emotional eating, eating control smoking, and drinking behaviors, while perceived stress is negatively related to health-promotion behavior (34).…”
Section: Figuresupporting
confidence: 93%
“…Social network support can effectively regulate individual behavior and enhance the sense of control over one's life to maintain good health. Li et al found that a high level of stress perception can hinder their health promotion behavior ability; the higher the perceived stress level, the lower the health promotion behavior ability (17).…”
Section: Introductionmentioning
confidence: 99%
“…A web questionnaires on the media use and psychological results of Chinese adults after the outbreak of the pandemic, as well as the relevant analysis results of foreign surveys after negative events such as "9.11", showed that negative media exposure was positively related to stress-related symptoms, such as anxiety, depression and worry [13,14]. Therefore, we speculated that during the pandemic, excessive negative media exposure may aggravate negative emotional reactions such as anxiety [15,16]. Accordingly, negative media exposure may be an important factor in causing negative emotions such as individuals' anxiety.…”
Section: Introductionmentioning
confidence: 95%